Statistical Optimization of Cellulase Production by A Novel Thermophilic Lignocellulolytic Bacterium Geobacillus stearothermophilus TP-3 from Tapovan Hot Spring in India - Meghna Arya; Garima Chauhan; Tazeem Fatima; Asha Kumari; Digvijay Verma; Monica Sharma (Journal of Pure and Applied Microbiology)
A novel thermophilic lignocellulolytic bacterium, Geobacillus stearothermophilus TP-3, was isolated and characterized from the Tapovan hot spring in India. The cellulase production of TP-3 was optimized using a One-Factor-at-a-Time (OFAT) approach followed by a Plackett-Burman design, leading to a three-fold enhancement in enzyme yield. Phylogenetic analysis based on 16S rRNA sequencing revealed high sequence similarity with Geobacillus sp. H6a. The cellulase enzyme exhibited optimal activity at 50 °C under alkaline conditions (pH 8.0) and retained ~68% of its activity across a broad temperature range (40-70 °C) for up to three hours, demonstrating remarkable thermo-alkali stability. The ANOVA revealed that three factors-glucose, carboxymethyl cellulose (CMC), and yeast extract-significantly affected cellulase production, with yeast extract emerging as the most influential factor. Notably, TP-3 efficiently degraded agronomic residues, including wheat bran and sugarcane molasses, highlighting its potential for sustainable agricultural waste valorization and bioethanol production. The exceptional thermostability and lignocellulolytic potential of G. stearothermophilus TP-3 position it as a promising candidate for industrial bioconversion processes.